Slavenski Jug ! leta 1848 in Slovenci - Podgoršek, Nataša (Zgodovinski časopis, 2002)
Slavenski Jug, Croatian nationalists' political newspaper, managed to acquire as its contributors prominent scientists, cultural and political personages whose work had strongly influenced the development of the Croatian political orientation. In 1848, they supported the principle of Austro-Slavicism and were in favor of the union of Croatian provinces with the Serbian Vojvodina and with Slovene provinces. That year, the Slavenski Jug newspaper published several plans proposing the union of these countries. The newspaper also published several reports from Slovene regions in which Slovenes voiced their support - moral as well as material - of the Croatian political movement. Slavenski Jug also published contributions on the activities of the Slavjansko društvo (Slavic Society) from Trieste, Italy, and on the activities of Styrian and Carinthian Slovenes. The newspaper also focused on the fights of Hungarian Serbs and Croats with Hungarians
Keywords: Croatia; Hrvaška; časopisi; Slavenski jug; časopisje; politični programi; history; zgodovina; nacionalizem; nationalism; 19.st.